PENGEMBANGAN LEGUMINOSA INDIGOFERA SEBAGAI PAKAN TERNAK DI NAGARI BATU PAYUNG KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Yesi Chwenta Sari; Syafri Nanda; Fatma Poni Mardiah; Roza Yunita (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Indigofera is a legume that can be used as forage for livestock. Leguminosa is a type of tree and shrub-shaped plant that contains higher protein than ordinary grass. Indigofera legumes have several advantages including high productivity, adaptability to low soil fertility, easy and inexpensive maintenance. This activity aims to transfer knowledge to farmers regarding the potential development of Indigofera legumes as quality animal feed and provide Indigofera legume seeds to be developed by members of farmer-livestock groups. This activity is a Community Service which was carried out at the Ambacang Permai livestock farmer group, Nagari Batu Payung, Lareh Sago Halaban District, Lima Puluh Kota Regency. The method used in this activity is counseling and socializing the potential of Indigofera legumes, as well as question and answer discussions regarding the development and how to plant Indigofera legumes. The results of this activity have provided additional knowledge for farmers in Nagari Batu Payung, Lareh Sago Halaban District regarding the potential for the development of Indigofera legumes because so far farmers only provide grass as animal feed. From the activities that have been carried out, it can be concluded that farmers in Nagari Batu Payung, Lareh Sago Halaban District are very helpful because through this activity farmers know the potential, how to plant and develop Indigofera as cattle feed. Breeders gave a positive response to the activities that had been carried out and hoped that Andalas University could assist independent groups in developing their cattle farming business.